2020
DOI: 10.1590/1518-8345.3655.3329
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a video on bed baths

Abstract: Objective: develop and validate a video on bed bathing directed to nursing professionals and students. Method: the video was based on the literature and presents the definition of bed bath, indications for its performance, steps to perform it, and potential complications. Nursing professors and nurses validated it. They assessed the pertinence of content, clarity, and language of the video scenes. The Delphi Technique was used in this phase. After recording, three nursing professors, along with undergraduate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
38

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(67 citation statements)
references
References 17 publications
3
26
0
38
Order By: Relevance
“…Studies point out that the construction of educational videos are good educational resources used by nursing, covering several areas: bed bath techniques (22) , aftercare-surgical procedures (23) , care Concerning the repetition of the scenarios, the changes of locations could compromise the sequence of the scenes. The teams also considered the logistics of the locations as impediments to not making changes in the recording environments.…”
Section: Discussionmentioning
confidence: 99%
“…Studies point out that the construction of educational videos are good educational resources used by nursing, covering several areas: bed bath techniques (22) , aftercare-surgical procedures (23) , care Concerning the repetition of the scenarios, the changes of locations could compromise the sequence of the scenes. The teams also considered the logistics of the locations as impediments to not making changes in the recording environments.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus in the literature regarding the number of judges needed for a validation study (22,(35)(36) . A literature review showed that some authors recommend a committee composed of at least 5 and at most 10 professionals with clinical experience in the field and working at the time of the research (22) .…”
Section: Population or Sample; Inclusion And Exclusion Criteriamentioning
confidence: 99%
“…A literature review showed that some authors recommend a committee composed of at least 5 and at most 10 professionals with clinical experience in the field and working at the time of the research (22) . Some studies that address content validation selected from 5 to 17 experts for the validation stage (29)(30)(31)33,(36)(37) .…”
Section: Population or Sample; Inclusion And Exclusion Criteriamentioning
confidence: 99%
“…In this scenario, health education actions supported by the use of educational technologies that address the concept of the disease, triggering factors, use of medicines and inhalation devices, signs and symptoms, as well as the identification and action in case of an exacerbation 6 are relevant for self-management. These educational technologies can be an effective alternative to support the dissemination of knowledge and autonomy of the person with asthma [7][8] .…”
Section: Development Of An Educational Booklet For Adults With Asthma...mentioning
confidence: 99%